Mutation‐specific antibody detects mutant BRAFV600E protein expression in human colon carcinomas. Issue 15 (8th May 2013) - Sinicrope, Frank A.; Smyrk, Thomas C.; Tougeron, David; Thibodeau, Stephen N.; Singh, Shalini; Muranyi, Andrea; Shanmugam, Kandavel; Grogan, Thomas M.; Alberts, Steven R.; Shi, Qian
<x xml:space="preserve">Abstract</x> BACKGROUND A point mutation (V600E) in the BRAF oncogene is a prognostic biomarker and may predict for nonresponse to anti‐EGFR antibody therapy in patients with colorectal carcinoma. BRAFV600E mutations are frequently detected in tumors with microsatellite instability and indicate a sporadic origin. We used a mutation‐specific antibody to examine mutant BRAFV600E protein expression and its concordance with BRAFV600E mutation data. METHODS Primary stage III colon carcinomas were analyzed for BRAFV600E mutations in exon 15, and 50 BRAFV600E mutation carriers and 25 wild‐type tumors were selected for analysis of BRAF proteins by immunohistochemistry (IHC). IHC was performed in archival tissue specimens using a pan‐BRAF antibody and a mutation‐specific antibody against BRAFV600E proteins. Staining was scored by 2 pathologists who were blinded to clinical and mutation data. RESULTS Using a pan‐BRAF antibody, total BRAF protein expression was observed in the tumor cell cytoplasm in 74 of 75 colon carcinomas. A mutation‐specific antibody identified diffuse cytoplasmic staining of mutant BRAFV600E proteins in 49 of 74 cancers. Analysis using a polymerase chain reaction‐based assay revealed that all 49 of these cancers carried BRAFV600E mutations. In contrast, BRAFV600E staining was absent in all 25 tumors that carried wild‐type copies of BRAF. CONCLUSIONS A BRAF mutation‐specific (V600E) antibody detected tumors with BRAFV600E mutations and exhibited complete concordance with a DNA‐based method. These results support the use of IHC as a simplified strategy to screen colorectal cancers for BRAFV600E mutations in clinical practice. Cancer 2013;119:2765–2770. © 2013 American Cancer Society.